Fluxing as a new tool for bitumen rheological characterization and the use of time-concentration shift factor (a c ) - Zoorob, Salah E. (2020)
The concept of temperature shift factor (aT) as defined by Doolittle, relating the free volume of a vis-coelastic material at the current and reference states is briefly examined together with the resultantWilliam-Landel-Ferry equation. This paper highlights the fact that change in free volume arise not onlyfrom temperature variations but can also result from the absorption of solvents and thus a generalizedDoolittle relation may also be applied to a solvent concentration shift factor (ac). To validate this concept,a small scale laboratory investigation was carried out by blending 40/60 penetration grade bitumen withvarious proportions of one type of cooking oil and conducting dynamic shear rheometer frequencysweeps at a range of temperatures. By applying time-concentration superposition to each flux content,it was possible to shift horizontally (ac) each set of complex modulus data measured at each test temper-ature, so that all sets superimpose onto the master curve of the base bitumen at a preselected referencetemperature. A direct relationship between conventional time-temperature shift and the proposed time-concentration shift factors was thus demonstrated using a sample of penetration grade bitumen and onetype of vegetable oil. Further experimentation with other bitumen-flux combinations is necessary priorto recommending general adoption of the proposed tool.